2022
DOI: 10.1186/s12889-022-13776-8
|View full text |Cite
|
Sign up to set email alerts
|

Feeding, caregiving practices, and developmental delay among children under five in lowland Nepal: a community-based cross-sectional survey

Abstract: Background Nurturing care, including adequate nutrition, responsive caregiving and early learning, is critical to early childhood development. In Nepal, national surveys highlight inequity in feeding and caregiving practices for young children. Our objective was to describe infant and young child feeding (IYCF) and cognitive and socio-emotional caregiving practices among caregivers of children under five in Dhanusha district, Nepal, and to explore socio-demographic and economic factors associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…As our data are from 2012, some changes in caregiving practices may have occurred. However, the gap in caregiving practices found here appears to have remained since a recent study conducted in Dhanusha district found similar ndings [25,29].…”
Section: Strengths and Limitationssupporting
confidence: 74%
See 2 more Smart Citations
“…As our data are from 2012, some changes in caregiving practices may have occurred. However, the gap in caregiving practices found here appears to have remained since a recent study conducted in Dhanusha district found similar ndings [25,29].…”
Section: Strengths and Limitationssupporting
confidence: 74%
“…We conducted a qualitative study in July 2012 to further explain ndings from quantitative research undertaken with the same study population [25] and generate a holistic understanding of cognitive and socio-emotional caregiving for children under three years in Dhanusha district, Nepal. The study was conducted by the local Non-governmental Organisation (NGO) Mother and Infant Research Activities (MIRA), Nepal, in collaboration with the Institute for Global Health, University College London, United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 11 In a similar study done in an urban population of Western Nepal, Midwestern Nepal and Eastern Nepal it was 72.7% and 67.2% respectively, which is more as compared to our study. 8 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Tanzania is inclusive with the problem of nutrition for under-five year children of which Tanzania Demographic and Health Survey data shows that 59% of infants are exclusively breastfed for six months, 39% of 6–24 months children are given minimum recommended meal frequency and 26 percent are given minimum recommended diverse diet [ 16 ]. Despite the huge progress achieved in the country yet, the majority of children are not fed at the Minimum Dietary Diversity (MDD) [ 17 ]. The most common food types caregivers feed children include 91% grains, roots, and tubers and 65% Vitamin A containing fruits and vegetables [ 18 ].…”
Section: Introductionmentioning
confidence: 99%